www.mathportal.

org
Integration Formulas
1. Common Integrals
Indefinite Integral
Method of substitution
( ( )) ( ) ( ) f g x g x dx f u du ′ =
∫ ∫

Integration by parts
( ) ( ) ( ) ( ) ( ) ( ) f x g x dx f x g x g x f x dx ′ ′ = −
∫ ∫

Integrals of Rational and Irrational Functions
1
1
n
n
x
x dx C
n
+
= +
+

1
ln dx x C
x
= +

c dx cx C = +

2
2
x
xdx C = +

3
2
3
x
x dx C = +

2
1 1
dx C
x x
= − +

2
3
x x
xdx C = +

2
1
arctan
1
dx x C
x
= +
+

2
1
arcsin
1
dx x C
x
= +

Integrals of Trigonometric Functions
sin cos x dx x C = − +

cos sin x dx x C = +

tan ln sec x dx x C = +

sec ln tan sec x dx x x C = + +

( )
2
1
sin sin cos
2
x dx x x x C = − +

( )
2
1
cos sin cos
2
xdx x x x C = + +

2
tan tan x dx x x C = − +

2
sec tan x dx x C = +

Integrals of Exponential and Logarithmic Functions
ln ln x dx x x x C = − +

( )
1 1
2
ln ln
1
1
n n
n
x x
x xdx x C
n
n
+ +
= − +
+
+

x x
e dx e C = +

ln
x
x
b
b dx C
b
= +

sinh cosh x dx x C = +

cosh sinh x dx x C = +

www.mathportal.org
2. Integrals of Rational Functions
Integrals involving ax + b
( )
( )
( )
( )
1
1
1
n
n
ax b
ax b dx
a
fo n
n
r
+
+
+ =
+
≠ −

1 1
ln dx ax b
ax b a
= +
+

( )
( )
( )( )
( ) ( )
1
2
1
1
2
,
1
2
n n
a n x b
x ax b dx ax b
a n n
for n n
+
≠ −
+ −
+ = +
+ +
≠ −

2
ln
x x b
dx ax b
ax b a
a
= − +
+

( )
( )
2 2 2
1
ln
x b
dx ax b
a ax b a
ax b
= + +
+
+

( )
( )
( )( )( )
( )
1
2
1
2
1
,
2
1
n n
a n x b
x
dx
ax b a n n
for n
ax b
n

− −
=
+

+ − −
≠ −

( )
( )
2
2
2
3
1
2 ln
2
ax b
x
dx b ax b b ax b
ax b
a
| |
+
|
= − + + +
| +
\ ¹

( )
2 2
2 3
1
2 ln
x b
dx ax b b ax b
ax b
a
ax b
| |
= + − + −
|
|
+
+ \ ¹

( ) ( )
2 2
3 3 2
1 2
ln
2
x b b
dx ax b
ax b
a
ax b ax b
| |
|
= + + −
| +
+ +
\ ¹

( )
( ) ( ) ( )
( )
3 2 1
2
2
3
2
1
3 2 1
1, 2, 3
n n n
n
ax b b a b b ax b
x
dx
n n
fo
n
a
r n
a
x b
− − −
| |
+ + +
|
= − + −
| − − −
+
\ ¹

( )
1 1
ln
ax b
dx
x ax b b x
+
= −
+

( )
2 2
1 1
ln
a ax b
dx
bx x
x ax b b
+
= − +
+

( )
( )
2 2 2 3
2
1 1 1 2
ln
ax b
dx a
x
b a xb ab x b
x ax b
| |
+
= − + − |
|
+
+
\ ¹

Integrals involving ax
2
+ bx + c
2 2
1 1 x
dx arctg
a a
x a
=
+

2 2
1
ln
1
2
1
ln
2
a x
for x a
a a x
dx
x a
x a
for x a
a x a
− ¦
<
¦
¦ +
=
´

¦
>
¦
+ ¹

www.mathportal.org

2
2 2
2
2
2
2 2
2
2 2
arctan 4 0
4 4
1 2 2 4
ln 4 0
4 2 4
2
4 0
2
ax b
for ac b
ac b ac b
ax b b ac
dx for ac b
ax bx c
b ac ax b b ac
for ac b
ax b
+ ¦
− >
¦
− −
¦
¦
+ − − ¦
= − <
´
+ +
− + + − ¦
¦
¦
− − =
¦ +
¹

2
2 2
1
ln
2 2
x b dx
dx ax bx c
a a
ax bx c ax bx c
= + + −
+ + + +
∫ ∫

( )
2 2
2 2
2 2
2
2 2
2 2
2 2
ln arctan 4 0
2
4 4
2 2
ln arctanh 4 0
2
4 4
2
ln 4 0
2 2
m an bm ax b
ax bx c for ac b
a
a ac b ac b
mx n m an bm ax b
dx ax bx c for ac b
a
ax bx c
a b ac b ac
m an bm
ax bx c for ac b
a a ax b
¦
− +
+ + + − >
¦
− − ¦
¦
+ − + ¦
= + + + − <
´
+ +
− − ¦
¦

¦ + + − − =
+
¦
¹

( )
( )
( )( )
( )
( )
( )
( )
1 1
2
2 2 2 2
2 3 2
1 2 1
1 4
1 4
n n n
n a
ax b
dx dx
n ac b
ax bx c n ac b ax bx c ax bx c
− −

+
= +
− −
+ + − − + + + +
∫ ∫

( )
2
2 2 2
1 1 1
ln
2 2
x b
dx dx
c c
ax bx c ax bx c x ax bx c
= −
+ + + + + +
∫ ∫

3. Integrals of Exponential Functions
( )
2
1
cx
cx
e
xe dx cx
c
= −

2
2
2 3
2 2
cx cx
x x
x e dx e
c
c c
| |
= − +
|
|
\ ¹

1
1
n cx n cx n cx
n
x e dx x e x e dx
c c

= −
∫ ∫

( )
1
ln
!
i
cx
i
cx
e
dx x
x i i

=
= +

( )
1
ln ln
cx cx
i
e xdx e x E cx
c
= +

( )
2 2
sin sin cos
cx
cx
e
e bxdx c bx b bx
c b
= −
+

( )
2 2
cos cos sin
cx
cx
e
e bxdx c bx b bx
c b
= +
+

( )
( )
1
2
2 2 2 2
1
sin
sin sin cos sin
cx n
cx n cx n
n n
e x
e xdx c x n bx e dx
c n c n

= − +
+ +
∫ ∫

www.mathportal.org
4. Integrals of Logarithmic Functions
ln ln cxdx x cx x = −

ln( ) ln( ) ln( )
b
ax b dx x ax b x ax b
a
+ = + − + +

( ) ( )
2 2
ln ln 2 ln 2 x dx x x x x x = − +

( ) ( ) ( )
1
ln ln ln
n n n
cx dx x cx n cx dx

= −
∫ ∫

( )
2
ln
ln ln ln
ln !
i
n
x
dx
x x
x i i

=
= + +

( ) ( )( ) ( )
( )
1 1
1
1
1
ln 1 ln ln
n n n
for n
dx x dx
n
x n x x
− −
= − +

∫ ∫

( )
( )
1
2
ln 1
n
1
1 l
1
m m
x
x xdx x
m
m
for m
+
| |
|
= −
| +
+
\ ¹

( )
( )
( ) ( )
1
1
ln
ln
1 1
1 ln
n
m
n n
m m
x x
n
x x dx x x dx
m
r
m
fo m
+

= − ≠
+ +
∫ ∫

( ) ( )
( )
1
ln ln
1
1
n n
x x
dx for n
x n
+
= ≠
+

( )
( )
2
ln
ln
0
2
n
n
x
x
dx for n
x n
= ≠

( )
( )
( )
1 2
1
ln ln 1
1
1
1
m m
m
x x
dx
x m x
m
for
x
m

= − −

( ) ( )
( )
( )
( )
1
1
ln ln n
1
l
1
1
n n n
m m m
x x x
n
dx dx
m
x m x x
for m

= − +

∫ ∫

ln ln
ln
dx
x
x x
=

( )
( ) ( )
1
1 ln
ln ln 1
!
ln
i i
i
n
i
n x
dx
x
i i
x x

=

= + −

( ) ( )( )
( )
1
1
ln 1 ln
1
n n
dx
x x n
f
x
or n

= −

( ) ( )
2 2 2 2 1
ln ln 2 2 tan
x
x a dx x x a x a
a

+ = + − +

( ) ( ) ( ) ( )
sin ln sin ln cos ln
2
x
x dx x x = −

( ) ( ) ( ) ( )
cos ln sin ln cos ln
2
x
x dx x x = +

www.mathportal.org
5. Integrals of Trig. Functions
sin cos xdx x = −

cos sin xdx x = −

2
1
sin sin 2
2 4
x
xdx x = −

2
1
cos sin 2
2 4
x
xdx x = +

3 3
1
sin cos cos
3
xdx x x = −

3 3
1
cos sin sin
3
xdx x x = −

ln tan
sin 2
dx x
xdx
x
=

ln tan
cos 2 4
dx x
xdx
x
π | |
= +
|
\ ¹

2
cot
sin
dx
xdx x
x
= −

2
tan
cos
dx
xdx x
x
=

3 2
cos 1
ln tan
sin 2sin 2 2
dx x x
x x
= − +

3 2
sin 1
ln tan
2 2 4 cos 2cos
dx x x
x x
π | |
= + +
|
\ ¹

1
sin cos cos 2
4
x xdx x = −

2 3
1
sin cos sin
3
x xdx x =

2 3
1
sin cos cos
3
x xdx x = −

2 2
1
sin cos sin 4
8 32
x
x xdx x = −

tan ln cos xdx x = −

2
sin 1
cos cos
x
dx
x x
=

2
sin
ln tan sin
cos 2 4
x x
dx x
x
π | |
= + −
|
\ ¹

2
tan tan xdx x x = −

cot ln sin xdx x =

2
cos 1
sin sin
x
dx
x x
= −

2
cos
ln tan cos
sin 2
x x
dx x
x
= +

2
cot cot xdx x x = − −

ln tan
sin cos
dx
x
x x
=

2
1
ln tan
sin 2 4 sin cos
dx x
x x x
π | |
= − + +
|
\ ¹

2
1
ln tan
cos 2 sin cos
dx x
x x x
= +

2 2
tan cot
sin cos
dx
x x
x x
= −

( )
( )
( )
( )
2 2
sin sin
sin sin
2 2
m n x m n x
mx nxdx
n m n
m n
m
+ −
− +
+ −
≠ =

( )
( )
( )
( )
2 2
cos cos
sin cos
2 2
m n x m n x
mx nxdx
n m n
m n
m
+ −
− −
+ −
≠ =

( )
( )
( )
( )
2 2
sin sin
cos cos
2 2
m n x m n x
mx nxdx
m n m n
m n
+ −
= +
+ −

1
cos
sin cos
1
n
n
x
x xdx
n
+
= −
+

1
sin
sin cos
1
n
n
x
x xdx
n
+
=
+

2
arcsin arcsin 1 xdx x x x = + −

2
arccos arccos 1 xdx x x x = − −

( )
2
1
arctan arctan ln 1
2
xdx x x x = − +

( )
2
1
arccot arccot ln 1
2
xdx x x x = + +

n ≠ −2 ) ∫ ax + b dx = a − a 2 ln ax + b b ∫ ( ax + b )2 dx = a 2 ( ax + b ) + a 2 ln ax + b ∫ ( ax + b )n dx = a 2 ( n − 1)( n − 2)( ax + b )n−1 x a (1 − n ) x − b x b 1 ( for n ≠ −1.org 2. n ≠ −2 ) 2  x2 1  ( ax + b )  dx = 3 − 2b ( ax + b ) + b 2 ln ax + b  ∫ ax + b  2 a    ∫ ( ax + b )2 ∫ ( ax + b )3 x2 x2 1  b2  dx = 3  ax + b − 2b ln ax + b −  ax + b  a    dx = 1  2b b2  ln ax + b + − ax + b 2 ( ax + b )2 a3       ∫ ( ax + b ) n 1 x2 dx = 3−n 2− n 1−n 2b ( a + b ) b2 ( ax + b ) 1  ( ax + b ) − + − n−3 n−2 n −1 a3       ( for n ≠ 1.www.3) ∫ x ( ax + b ) dx = − b ln 1 1 1 ax + b x ∫ x 2 ( ax + b ) dx = − bx + b2 ln ∫ x 2 ( ax + b )2 1 1 a ax + b x      1 1 2 ax + b dx = − a  2 + 2 − 3 ln  b ( a + xb ) ab x b x  Integrals involving ax2 + bx + c ∫ x 2 + a 2 dx = a arctg a 1 1 x a−x 1  2a ln a + x  ∫ x2 − a 2 dx =  1 x − a  ln  2a x + a  for x < a for x > a . 2. Integrals of Rational Functions Integrals involving ax + b ( ax + b )n + 1 ∫ ( ax + b ) dx = a ( n + 1) n ( for n ≠ −1) ∫ ax + b dx = a ln ax + b ∫ x ( ax + b ) x n 1 1 dx = a x a ( n + 1) x − b 2 ( n + 1)( n + 2 ) ( ax + b )n+1 ( for n ≠ −1.mathportal.

mathportal.org 2 2ax + b  arctan  2 4ac − b 2  4ac − b  1 2 2ax + b − b 2 − 4 ac  dx =  ln ∫ ax 2 + bx + c  b 2 − 4ac 2 ax + b + b 2 − 4ac  − 2  2ax + b  for 4ac − b 2 > 0 for 4ac − b 2 < 0 for 4ac − b 2 = 0 ∫ ax 2 + bx + c dx = 2a ln ax x 1 2 + bx + c − b dx ∫ ax 2 + bx + c 2a m 2an − bm 2ax + b 2 arctan for 4ac − b 2 > 0  ln ax + bx + c + 2 2 2a a 4ac − b 4ac − b  m mx + n 2an − bm 2ax + b  2 2 ∫ ax 2 + bx + c dx =  2a ln ax + bx + c + a b2 − 4ac arctanh b2 − 4ac for 4ac − b < 0  m 2an − bm  ln ax 2 + bx + c − for 4ac − b 2 = 0 a ( 2 ax + b )  2a  ∫ 1 ( ax 2 + bx + c 1 ) n dx = 2ax + b ( n − 1) ( 4ac − b2 )( ax 2 + bx + c ) n−1 + ( 2 n − 3 ) 2a 1 dx 2 ∫ ( n − 1) ( 4ac − b ) ( ax 2 + bx + c )n−1 ∫x ( ax 2 + bx + c ) dx = 1 x2 b 1 ln 2 − ∫ 2 dx 2c ax + bx + c 2c ax + bx + c 3.www. Integrals of Exponential Functions cx ∫ xe dx = ecx c2 ( cx − 1)  x2 2x 2  x 2 ecx dx = ecx  ∫  c − c 2 + c3     ∫x n cx e dx = 1 n cx n n −1 cx x e − ∫ x e dx c c i ∞ cx ( ) ecx dx = ln x + ∑ ∫ x i =1 i ⋅ i ! ∫e cx ln xdx = 1 cx e ln x + Ei ( cx ) c ecx c 2 + b2 ecx c 2 + b2 c +n 2 cx ∫ e sin bxdx = cx ∫ e cos bxdx = cx n ∫ e sin xdx = ( c sin bx − b cos bx ) ( c cos bx + b sin bx ) 2 ecx sin n −1 x ( c sin x − n cos bx ) + n ( n − 1) c +n 2 2 ∫e cx sin n −2 dx .

www. Integrals of Logarithmic Functions ∫ ln cxdx = x ln cx − x ∫ ln(ax + b)dx = x ln(ax + b) − x + a ln(ax + b) ∫ ( ln x ) dx = x ( ln x ) − 2 x ln x + 2 x n n n −1 ∫ ( ln cx ) dx = x ( ln cx ) − n∫ ( ln cx ) dx ∞ ln x ( ) dx = ln ln x + ln x + ∑ ∫ ln x n =2 i ⋅ i ! i 2 2 b ∫ ( ln x )n dx =− x ( n − 1)( ln x ) n −1 + 1 dx n − 1 ∫ ( ln x )n −1 ( for n ≠ 1)  ln x 1 x m ln xdx = x m +1  − ∫  m + 1 ( m + 1) 2      ( for m ≠ 1) ( for m ≠ 1) ∫ x ( ln x ) m n dx = x m+1 ( ln x ) m +1 n − n n −1 m ∫ x ( ln x ) dx m +1 ∫ ( ln x )n x dx = ( ln x )n+1 n +1 ( for n ≠ 1) ln x n ln x n ( for n ≠ 0 ) ∫ x dx = 2n ln x ln x 1 ∫ xm dx = − ( m − 1) xm−1 − ( m − 1)2 xm−1 ( ) 2 ( for m ≠ 1) ( for m ≠ 1) ∫ ( ln x )n xm dx ( ln x )n ( ln x )n−1 n dx = − + dx ( m − 1) x m−1 m − 1 ∫ x m ∫ x ln x = ln ln x ∫ xn ln x = ln ln x + ∑ ( −1) i =1 ∫ x ( ln x )n ∫ ln ( x 2 dx ∞ i ( n − 1)i ( ln x )i i ⋅ i! dx =− 1 ( n − 1)( ln x )n−1 ( for n ≠ 1) + a 2 dx = x ln x 2 + a 2 − 2 x + 2a tan −1 x ) ( ) x a ∫ sin ( ln x ) dx = 2 ( sin ( ln x ) − cos ( ln x ) ) ∫ cos ( ln x ) dx = 2 ( sin ( ln x ) + cos ( ln x ) ) x .org 4.mathportal.

www.org 5. Integrals of Trig.mathportal. Functions ∫ sin xdx = − cos x ∫ cos xdx = − sin x x 1 − sin 2 x 2 4 x 1 2 ∫ cos xdx = 2 + 4 sin 2 x 1 3 3 ∫ sin xdx = 3 cos x − cos x 1 3 3 ∫ cos xdx = sin x − 3 sin x ∫ sin 2 x dx = − sin x cos 2 x x ∫ sin x dx = ln tan 2 + cos x cos x 1 ∫ sin 2 xdx = ∫ cot 2 xdx = − cot x − x ∫ sin x cos x = ln tan x ∫ sin 2 x cos x = − sin x + ln tan  2 + 4    ∫ sin x cos2 x = cos x + ln tan 2 ∫ sin 2 x cos2 x = tan x − cot x dx dx dx 1 x π dx 1 x ∫ sin x xdx = ln tan 2 ∫ cos x xdx = ln tan  2 + 4    dx ∫ sin 2 x xdx = − cot x dx ∫ cos2 x xdx = tan x dx x dx x π ∫sin mxsin nxdx = − 2( m+ n) sin( m + n) x sin( m − n) x + 2( m − n) cos ( m + n) x cos ( m − n) x − 2( m − n) m2 ≠ n2 m2 ≠ n2 m2 ≠ n2 ∫sin mxcos nxdx = − 2( m + n) ∫ cos mxcos nxdx = 2( m + n) n ∫ sin x cos xdx = − n ∫ sin x cos xdx = dx cos x 1 x ∫ sin 3 x = − 2sin 2 x + 2 ln tan 2 dx sin x 1 x π ∫ cos3 x = 2 cos2 x + 2 ln tan  2 + 4    1 ∫ sin x cos xdx = − 4 cos 2 x 1 3 2 ∫ sin x cos xdx = 3 sin x 1 2 3 ∫ sin x cos xdx = − 3 cos x x 1 2 2 ∫ sin x cos xdx = 8 − 32 sin 4 x sin ( m + n) x sin ( m − n) x + 2( m − n) cos n +1 x n +1 sin n +1 x n +1 1 − x2 1 − x2 1 2 ∫ arcsin xdx = x arcsin x + ∫ arccos xdx = x arccos x − ∫ arctan xdx = x arctan x − 2 ln ( x 1 +1 ) ∫ tan xdx = − ln cos x ∫ cos sin x 1 dx = 2 cos x x ∫ arc cot xdx = x arc cot x + 2 ln ( x 2 +1 ) sin 2 x x π  ∫ cos x dx = ln tan  2 + 4  − sin x   ∫ tan xdx = tan x − x ∫ cot xdx = ln sin x 2 .